2021
DOI: 10.1038/s41598-021-88157-z
|View full text |Cite
|
Sign up to set email alerts
|

C subunit of the ATP synthase is an amyloidogenic calcium dependent channel-forming peptide with possible implications in mitochondrial permeability transition

Abstract: The c subunit is an inner mitochondrial membrane (IMM) protein encoded by three nuclear genes. Best known as an integral part of the F0 complex of the ATP synthase, the c subunit is also present in other cytoplasmic compartments in ceroid lipofuscinoses. Under physiological conditions, this 75 residue-long peptide folds into an α-helical hairpin and forms oligomers spanning the lipid bilayer. In addition to its physiological role, the c subunit has been proposed as a key participant in stress-induced IMM perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Figure 1A shows a representative trace of the c subunit oligomers at 50 mV. This channel activity is in good agreement with previously reported activity of the unmodified peptide [8]. In order to study the effect of CypD on the electrophysiological activity of the c subunit, we dissolved the lyophilized peptide in the same buffer as above, but this time, it was supplemented with 0.41 mg/mL of CypD.…”
Section: Cypd Induces the Formation Of High-conductive C Subunitsupporting
confidence: 87%
See 2 more Smart Citations
“…Figure 1A shows a representative trace of the c subunit oligomers at 50 mV. This channel activity is in good agreement with previously reported activity of the unmodified peptide [8]. In order to study the effect of CypD on the electrophysiological activity of the c subunit, we dissolved the lyophilized peptide in the same buffer as above, but this time, it was supplemented with 0.41 mg/mL of CypD.…”
Section: Cypd Induces the Formation Of High-conductive C Subunitsupporting
confidence: 87%
“…This mechanism is supported by studies that showed that the c subunit alone is sufficient to induce PTP [6,12,14]. Our recent report showed that the unmodified c subunit is an amyloidogenic peptide that spontaneously folds into cross-β oligomers and offers a potential mechanism on how such pores can form [8]. One of the defining features of the channel candidate for involvement in PTP is its dependence on CypD, an endogenous mitochondrial chaperone and well-established activator of PTP [16].…”
Section: Cypd Induces the Formation Of High-conductive C Subunitmentioning
confidence: 78%
See 1 more Smart Citation
“…The CsA can inhibit the mPTP opening at an early stage but not at later ones. The c subunits could also form an ion channel by assembling into oligomers in a β-sheet conformation with a similar mechanism to some other amyloidogenic peptides that form a β-sheet oligomeric pore [19]. Recently, it has been suggested that CyPD-c subunit interactions help the formation of higher-order oligomers, but is not required for pore activity by highlighting the folding activity in the mPTP formation [20].…”
mentioning
confidence: 99%
“…Several proteins such as VIDAC, ANT and CypD have been considered a potential forming channel but robust results are for ATP synthase dimers or its c-ring, the major component of the membrane FO complex of the enzyme, as the core channel of mPTP [50,101,102]. Indeed, high Ca 2+ concentration inhibits the organization of c subunit in fibrils and induces the formation of cross-β oligomers, able to form small channels in model lipid bilayers [50,101,101,103,104].…”
Section: Neurodegenerationmentioning
confidence: 99%